Peran Dimensi Kualitas Layanan Terhadap Kepuasan Nasabah Pada Bank BRI Kantor Kas Universitas Islam Malang - Adhien Azka Arifatul Ula; Nur Hidayati; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the role of service quality dimensions on customer satisfaction of Bank BRI Cash Office of Islamic University of Malang. The data used in this study used primary data by distributing research questionnaires to respondents. The population of this study was customers of Bank BRI Cash Office of Islamic University of Malang, while the sample in this study was 98 respondents. The sampling method in this study uses non-probability sampling, namely accidental sampling. The analytical method used in this study is simple linear analysis with hypothesis testing using t test. Research shows that the dimensions of service quality consisting of tangibles, reliability, responsiveness, assurance and empathy have a significant effect on customer satisfaction. Keywords: Keywords: Service Quality Dimension, Customer Satisfaction